"Naprzód przyszedł Mikołaj Rej". O literaturze niepodległej Polski w epistolograficznej refleksji Elizy Orzeszkowej = "Mikołaj Rej has come first". On literature of independent Poland in epistolographic reflections by Eliza Orzeszkowa - Sikora, Ireneusz (1952-2016) (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The synthetic study brings effects of Eliza Orzeszkowa's letters thorough analysis (gathered and published by Edward Jankowski in nine volumes), which contained information on her reading experiences. As it appears, she read a lot and of course she was familiar with many old Polish and Enlightenment literary masterpieces. Her correspondences have become a durable proof of her reading passion. Orzeszkowa held in her hands texts written by Biernat of Lublin.
Keywords: Orzeszkowa, Eliza (1841-1910); epistolografia; recepcja; literatura polska - do 1795 r.; epistolography; reception; Polish literature (up to 1795)